Explorando a informática educativa como alternativa de ensino da geometria plana na educação básica - Saúgo, Caroline (2016)
This study belongs to the research line: Information Technologies, Communication and Interaction Applied to the Teaching of Science and Mathematics, from the Graduate Program in Science and Mathematics Teaching (PPGECM); and the research line Technology and Digital Inclusion Methodologies from the Group of Study and Research on Digital Inclusion. It has, as its input, the contents of plane geometry, specifically in the eighth year of elementary school. Its goal is to explore the potential of computer programming for the understanding of the notable quadrilaterals, from a didactic sequence created specifically to this purpose. In this proposal, recorded and systematized in a blog, the teacher acts as a knowledge mediator, guiding students and providing meaningful and active learning. The methodological procedures were developed during math classes where students used web resources to search for concepts and figures, systematized and made a collective presentation using Google Drive, where it was possible for the students to interact and express their ideas. Thus, a seminar was held with the class so that the students could show their understanding and the teacher could intervene with formal mathematical concepts. To conclude the activities, the students used computer programming with the software Scratch, which was the last task of the sequence. Methodologically it is characterized, depending on the general purpose, as qualitative, having as data collection instruments questionnaires applied using Google Drive and videos of the didactic application for analysis. Through the analysis, it was noticed that the Information and Communication Technologies (ICT), especially the programming software, can assist in the development of logical reasoning in students' motivation to learn something new and in the understanding of mathematical concepts, making the process of teaching and learning more meaningful and enjoyable.